Algorithmic Regulation, Justice, and Labor Competitiveness: The Impact of the Artificial Intelligence Regulation in Latin America - Bracho-Fuenmayor, Pedro Luis; Arcia-Hernández, Pedro; Pérez-Vargas, Reina Marlene; Espíritu-Martínez, Antony Paul; Abad-Paguay, Andrés Vicente; Cahuana-Tapia, Rogelio Domingo; Paguay-Chávez, Félix Wilmer; Eguigure-Torres, Yenny Aminda; Casanueva-Yáñez, Galvarino (Journal of Posthumanism, 2025)
The purpose of this article was to analyze the incidence of the Artificial Intelligence Regulation on the Labor Competitiveness of companies in the Latin American context, due to the emerging regulation that AI merits on data protection, privacy and public use in a convergent way, gathering information from the literature, so the study method was narrative with support in systematic reviews of information sources, from a qualitative approach documentary type of bibliographic design, using the technique of content analysis to compare findings between authors. As a result, it was evidenced the wide margin of intervention that is required with RIA to verify the validity of legal implementation of its usability in replacement of the worker's adaptability to its labor use, which would contribute to evaluate the scenarios where the processes of labor training in AI are audited; thus concluding on the need to have the main functions of scientific, ethical, moral, transparent and transparent criteria and with a record of processed data on the content of information from third parties to companies and institutions where the AI modeled system can be adopted to improve labor competitiveness.